Timing and recurrence intervals for voluminous silicic eruptions from Amatitlán caldera (Guatemala). (1st February 2023) - Cisneros de León, A.; Danišík, M.; Schindlbeck-Belo, J.C.; Kutterolf, S.; Schmitt, A.K.; Freundt, A.; Kling, J.; Wang, K.-L.; Lee, H.-Y.
Abstract: Defining a precise timeline for past eruptions from explosive volcanoes in continental arcs is imperative to forecast future hazards and mitigate volcanic disasters in these often densely populated regions. However, establishing reliable ages for Quaternary eruptions in the Central American Volcanic Arc has been challenging due to the common lack or alteration of suitable K-rich phases for 40 Ar/ 39 Ar geochronology, but also from their position in time beyond the reach of 14 C dating. This especially holds for the active Amatitlán caldera in Guatemala, from which at least six explosive silicic eruptions have produced tephra blanketing neighboring regions that are today inhabited by millions of people. Zircon, a common datable accessory mineral in Amatitlán caldera magmas, is used here to retrieve eruption ages by applying the novel zircon double-dating method (ZDD) that integrates 238 U– 230 Th disequilibrium dating and (U–Th)/He thermochronology. This approach yielded the first-ever radioisotopic ages of 24 ± 3 ka and 48 ± 6 ka (1σ), respectively, of two of Amatitlán caldera's most recent eruptions (J-tephra and E-tephra). Remarkably, both zircon crystallization and ZDD eruption ages for the older and voluminous T-tephra and L-tephra units significantly post-date existing plagioclase 40 Ar/ 39 Ar dates by ca. 26 and 70 kyr, respectively. The ZDD eruption age for T-tephra is 93 ± 4 ka, whereas zircon crystallization ages for L-tephra yield a maximum model eruption age of ca. 124 ka. The strong eruption age divergence between ZDD and plagioclase 40 Ar/ 39 Ar dating argues for the presence of inherited or xenocrystic plagioclase in Amatitlán caldera eruptive products. Statistical analysis based on the updated eruptive history suggests a recurrence interval of ca. 17 kyr, which is significantly shorter than previously estimated. The new age data, thus, suggest a more frequent eruptive activity of Amatitlán caldera than formerly thought and underscores the necessity to better understand the current underlying magmatic system and to constrain its past eruptive history more precisely. Highlights: New and updated ages for explosive eruptions from Amatitlán caldera. Zircon double-dating suggests a much younger eruptive history. Existing plagioclase Ar eruption ages are ca. 26 to 70 kyr older than ZDD. New eruption history suggests a shorter recurrence interval of ca. 17–24 kyr.